Allegories of the Campus in Polish Academic Narratives - Kraszewska, Marzena (Respectus Philologicus, 2018)
[full article and abstract in English] In the paper, two Polish academic narratives Krzysztof Zanussi’s movie “Camouflage” (“Barwy Ochronne”) of 1976, and Wit Szostak’s novel “A Hundred Days Without Sunshine” (“Sto dni bez słońca”) of 2014 are discussed from the perspective of the use of the campus space as an image of the state. Drawing from the tradition of the British and American campus novel – a literary genre that developed in the 1950s and reached the peak of its popularity in the 1990s, the two narratives, created in two different political realities, make use of the absence of academic campuses in Poland and offer the campus as a miniature of the social space of the state in which conflicting ideas and ideologies clash, revealing the mechanisms of meritocratic privileging and hierarchization of positions. Such elements as imagery, the presentation of characters, forms of narration, literary / film techniques, use of language are analysed in order to show that they are used by the authors to stress an allegorical meaning in the analysed narratives.